Coal desulfurization by photocatalytic oxidation in the presence of [HO2MMim][HSO4] and H2O2. (15th December 2021) - Wang, Lanyun; Wen, Xinglin; Liu, Zhen; Liu, Zejian; Zhang, Yajuan; Lu, Xiaoran; Zhou, Huajian; Xu, Yongliang
Highlights: After photocatalytic treatment, the content of thiophene in coal was reduced. The burning time of coal sample after photocatalytic desulfurization is shortened. Through the DFT calculation, it is found that thiophene is easily oxidized into sulfone. Abstract: Photocatalytic oxidation has been widely used in sulfur oxidation due to its mild reaction conditions. In order to improve the efficiency of removing sulfur from coal, especially the organic sulfur, TiO2, SiO2 and modified SiO2 were used as photocatalysts under UV lamp irradiation in the presence of 1-carboxymethyl-3-methylimidazole bisulfite ([HO2 MMim][HSO4 ]) and hydrogen peroxide (H2 O2 ). The results show that the photocatalysts played important roles in coal desulfurization. The desulfurization rate of [HO2 MMim][HSO4 ]–H2 O2 (1:10) treatment on coal was only 16.89%, while after adding TiO2, e.g. [HO2 MMim][HSO4 ]–H2 O2 -TiO2 (1:10:4), it increases to 38.46% and the removing rate of organic sulfur approached 20.17% under normal temperature and pressure on a basis of photocatalysis. According to FTIR and XPS measurements, it is found that the catalytic oxidation can be accelerated in the presence of photocatalysts under ultraviolet irradiation, and the thiophene conversion can be enhanced significantly. Generally, TiO2 is more efficient in organic sulfur removal than SiO2 during photocatalytic oxidation. The results of quantum chemistry calculation indicates that thiophene sulfone could be produced much easier than the thiophene ring-cleaved reaction when thiophene was oxidized in the presence of hydroxyl radicals. In addition, compared to the traditional methods, the photocatalytic desulfurization only show a slight reduction of combustion heat value according to TG-DSC-DDSC measurements.